Напис про смерть Ярослава Мудрого у Софійському соборі в Києві та деякі питання його вивчення - Висоцький, С.О. (Археологія, 1991)
У статті розглядається прочитання і датування напису про смерть Ярослава Мудрого
з Софійського собору в Києві. В статье рассматриваются чтение и датировка записи о смерти Ярослава Мудрого 20 февраля 1054 г. из Софийского собора в Киеве. Анализируются высказывания по этому вопросу В. К. Зибарова, предложившего иное чтение даты события. Доказывается неубедительность и несостоятельность предложенной аргументации.
В статье также идет речь о стилях летоисчисления в надписи-граффити из собора и в сообщении «Повести временных лет» об этом событии. Делается вывод, что в летописи и в граффити в сообщении о смерти Ярослава Мудрого применен не мартовский, а византийско-сентябрьский стиль летоисчисления. Это можно объяснить влиянием записей в княжеском синодике, который велся при митрополии — Софийском соборе. The paper considers reading and dating of the inscription about the death of Jaroslav, the Wise on February 20, 1054 from Sofia Cathedral in Kiev. V, K. Zibarov statements concerning this problem are analyzed. He suggested another reading of the event date. The suggested arguments are proved unconvincing and inconsistent.
Style of chronology in inscription of graffiti from the Cathedral and in communication of «Chronicles of Years That Passed» about this event are reported. A conclusion is made that in chronicles and in graffiti in communication about the death of Jaroslav, the Wise there was applied not the March but the Byzantine September style of chronology. It may be explained by the influence of the records in the Prince’s synodic which was kept at metropolia — the Sofia Cathedral.